Pengaruh Metode Demonstrasi terhadap Keterampilan dalam Pembuatan Pemberian Makanan Tambahan (PMT) Berbasis Lokal pada Ibu Kader Kesehatan: The Influence of Demonstration Methods on the Skills of Community Health Cadres in Preparing Locally Based Suplementary Foods - Dewi Kartika Sari; Fredlina Rossa Balindra; Nadia Taqqiya (Jurnal Keperawatan Berbudaya Sehat, 2026)
Childhood nutrition have a crucial role in building a healthy and high-quality generation. One effective approach to improving the nutritional status of children under five is through the provision of nutritious locally-based supplementary food (PMT). This study aims to analyze the impact of the demonstration method on the skills of community health cadres mothers in preparing locally-based PMT. The study employs a pre-experimental design with a pre-posttest approach, involving 20 community health cadres mothers as respondents. The training was conducted in October 2025, focusing on processing moringa leaves into nutritious PMT. The training began with presentation followed by a demonstration of processing local ingredients so that the cadres could gain skills to share with the community. Skill assessments were carried out before and after the training using the Wilcoxon statistical test. The results indicate that most respondents experienced an improvement in skills, with 12 respondents (60%) showing significant skill enhancement after the intervention. The statistical test, with a p-value of 0.000, shows that the demonstration method has a significant effect on improving the skills of community health cadres mothers in preparing locally-based PMT. The study concludes that the demonstration method is effective in enhancing the practical skills of community health care mothers in preparing nutritious PMT for children under five, and it can be implemented in community-based nutritional empowerment programs using local resources.